Розробка нечіткого алгоритму регулювання коефіціентів несиметрії напруги за зворотною і нульовою послідовностями - Панов, А. О.; Гриценко, С. Д.; Галько, Сергій Віталійович; Panov, A.; Hrytsenko, S.; Halko, Serhii (Запоріжжя : 2024, 2024)
UA: У цій роботі наведено результати дослідження застосування нечітких алгоритмів керування для нормалізації коефіцієнтів несиметрії напруги за зворотною і нульовою послідовностями в електромережі. Розроблено моделювання системи у нечіткій логіці, де представлено функції приладдя для термі вхідної і вихідної змінних. Представлене графічне регулювання правил вхідних змінних, де чітко видно перемикання комутації Наведені евристичні знання аналізованої проблемної галузі логічного висновку для нормалізації коефіцієнтів несиметрії напруги по зворотній та нульовій послідовності. Показано ефективність представлених алгоритмів з урахуванням моделювання. EN: The article is formulated the results of the study of the use of fuzzy control algorithms for the normalization of voltage asymmetry coefficients for reverse and zero sequences in the power grid. The problem of three-phase electrical networks with a voltage of 0.4 kV is presented. It was found that the asymmetry of the voltage is expressed in the inequality between the modules of the phase voltage vectors and the shift angles between them. It was found in the problem that voltage asymmetry leads to a sharp decrease in the efficiency of three-phase asynchronous motors. Asynchronous motors, which constitute the largest part of the industrial loads of the system, were studied. An analysis of the latest research was carried out. The option of eliminating voltage asymmetry in rural electric networks due to the use of special devices for symmetrizing the power line is considered. Considered another option to eliminate voltage asymmetry due to equalization of the load by phases. A technical solution to this method was found in the introduction of an additional interphase variable resistance. The last considered technical solution was equalization of the load by phases with the introduction of a balancing device of the transformer type. The purpose of the study was formed to improve the quality of electricity by adjusting the voltage asymmetry coefficients in reverse and zero sequence. Modeling of the system in fuzzy logic is developed, where the input and output variable terms are presented. The graphical regulation of the rules of the input variables is presented, where the switching of the commutation is clearly visible. Heuristic knowledge of the analyzed problem area of the logical conclusion for the normalization of the voltage asymmetry coefficients in the reverse and zero sequence is presented. A fuzzy output surface view GUI for switching switching is demonstrated. The effectiveness of the presented algorithms is shown, taking into account modeling.
Development of a fuzzy algorithm for regulating coefficients of voltage unsymmetry by reverse and zero sequences
Keywords: якість електроенергії; коефіцієнт несиметрії напруги; нечіткість; алгоритм регулювання; зворотна та нульова послідовності; power quality; voltage asymmetry coefficient; uncertainty; regulation algorithm; reverse and zero sequence